2005
DOI: 10.1111/j.1365-2249.2005.02887.x
|View full text |Cite
|
Sign up to set email alerts
|

Does soluble triggering receptor expressed on myeloid cells-1 play any role in the pathogenesis of septic shock?

Abstract: SummaryIn order to define the significance of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) upon progression from sepsis or severe sepsis to septic shock a prospective study was designed with 90 enrolled patients with septic syndrome due to ventilator-associated pneumonia. Blood was sampled on seven consecutive days upon initiation of symptoms and concentrations of tumour necrosis factor-alpha (TNFa a a a ), interleukin-6 (IL-6), IL-8 and sTREM-1 were estimated in serum by an enzymeimmunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 17 publications
4
32
0
10
Order By: Relevance
“…This finding is compatible with overall lower leukocyte activation in the presence of Ang-2 or altered leukocyte distribution between peritoneum, blood, and tissues (Routsi et al, 2005).…”
supporting
confidence: 77%
“…This finding is compatible with overall lower leukocyte activation in the presence of Ang-2 or altered leukocyte distribution between peritoneum, blood, and tissues (Routsi et al, 2005).…”
supporting
confidence: 77%
“…This raises the question of the true concentration of sTREM-1 in plasma. To our knowledge, 4 studies have quantified sTREM-1 in plasma/serum (7,22,31,32 ). There is a 400-fold difference in the LOD among the assays used in the 4 studies, but this difference did not influence their abilities to quantify sTREM-1 in serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of TREM-1 immediately induces rapid degranulation of neutrophilic granules and drives the release of proinflammatory factors, including MIP-1, MCP-1 and IL-8, thus playing an important regulatory role in inflammation (22). sTREM-1, the soluble form of TREM-1, has been demonstrated to be produced and secreted into body fluids including blood during microbial infections, and its expression level is closely associated with the severity of infection, including HAP caused by A. baumannii (11,23). It is worth noting that the specificity of sTREM-1 in bacterial infection still remains controversial.…”
Section: Discussionmentioning
confidence: 99%